The role of social capital in expanding retail platform ecosystems - HE, Tong; Liu, Martin J.; Phang, Chee Wei (2020)
In the past few years, the discussion on platform ecosystems has become pervasive in strategy and information system research. Previous studies underlie the transformational nature of digital infrastructure in expanding the ecosystem. In this paper, the authors focus on the retail sector, where online retail platform owners such as Amazon and Alibaba are contending for ecosystem members and expanding by making them more physical. As ecosystem members have traditionally coordinated their network activities and resources embedded in an enabling social context, this study aims to investigate the influence of preexisting social capital possessed by ecosystem members on expansion of retail platform ecosystems. This dimension has received little attention thus far. Based on some conceptual basis discussed by extant literature and some preliminary empirical findings through our case study on Alibaba Lingshoutong (LST), a growing retail platform ecosystem, we have proposed some future research directions. © Proceedings of the 24th Pacific Asia Conference on Information Systems: Information Systems (IS) for the Future, PACIS 2020. All rights reserved.